A virtual environment for learning to view during aerial movements - Yeadon, M. R.; Knight, J. P. (Computer Methods in Biomechanics and Biomedical Engineering, 2012)
Training the gymnasts to view the landing area when learning aerial skills may lead to more consistent landings but can be problematic and potentially dangerous. A virtual environment allowing gymnasts to get introduced to viewing techniques safely is presented. The system is based on existing simulation models and visualisation software, and is implemented using client-server technology to allow reuse with new simulation models in the future.